AKNA as Genetic Risk Factor for Cervical Intraepithelial Neoplasia and Cervical Cancer - Torres-Poveda, Kirvis; Burguete-García, Ana I.; Bahena-Román, Margarita; Lagunas-Martínez, Alfredo; Madrid-Marina, Vicente (IntechOpen, 2012)
None